Interaksi Komunikasi dalam Pendidikan - Ahmad Taufik (Edification Journal : Pendidikan Agama Islam, 2020)
Through communication is the act of carrying out contact between the sender and the recipient, with the help of a message; the sender and recipient have several shared experiences that give meaning to the message and symbol sent by the sender, and are received and interpreted by the recipient. In the world of education, communication is carried out by teachers and students. To create effective communication. Almost every time the teacher communicates with teachers, friends, and parents. Communication with students will be different from fellow teachers, and parents. Communication skills in question can be the ability to understand and design information, choose and use channels or media, and interpersonal communication skills in the learning process. Learning interactions must be created so that students can be interested and fun to learn.